2019
DOI: 10.3389/fphys.2019.01159
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation on Parietal Operculum Contralateral to the Moving Limb Does Not Affect the Programming of Intra-Limb Anticipatory Postural Adjustments

Abstract: Recent data suggest that the parietal operculum acts as an integration center within a multimodal network, originating from different primary sensory and motor cortices and projecting to frontal, parietal and temporal cortical hubs, which in turn govern cognitive and motor functions. Thus, parietal operculum might also play a crucial role in the integrated control of voluntary movement and posture. As a first step to test this hypothesis, the Anticipatory Postural Adjustments (APAs) stabilizing the arm when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…In particular, Fujimoto et al (2017) reported that dh-tDCS over the POs, with the same 2 mA intensity used in the present study, actually produced a greater improvement in tactile orientation discrimination than the uni-hemisphere tDCS. Nevertheless, we did not observe any significant effect of dh-tDCS on amplitude or latency of intra-limb APAs associated with the index-finger flexion, in this way mimicking the results and confirming the conclusion of our previous work ( Marchese et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, Fujimoto et al (2017) reported that dh-tDCS over the POs, with the same 2 mA intensity used in the present study, actually produced a greater improvement in tactile orientation discrimination than the uni-hemisphere tDCS. Nevertheless, we did not observe any significant effect of dh-tDCS on amplitude or latency of intra-limb APAs associated with the index-finger flexion, in this way mimicking the results and confirming the conclusion of our previous work ( Marchese et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…We focused on PO as an important hub able to integrate multisensory streams within the motor organization ( Milner et al, 2007 ; Sepulcre, 2014 ). Even though our recent work ( Marchese et al, 2019 ) demonstrated that anodal or cathodal tDCS limited to the PO contralateral to the moving finger (coPO) did not disturb the APAs, here, we bilaterally stimulated both POs with opposite currents (dh-tDCS) as this approach has been proved to produce stronger effects than the unilateral stimulation in several neuromodulation studies. Dh-tDCS has been described to be a proficient tool to improve cerebral functionality ( Vines et al, 2008 ) and to be more effective with respect to the uni-hemisphere approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of an excitatory or inhibitory EMG change was identified by a software algorithm, which searched the first time point in which the track fell above or below 2 SD of the reference signal (excitation or inhibition, respectively) and remained there for at least 50 ms. Whenever the criterion was met, the algorithm searched backward the point in which the signal started to deviate from the mean reference value [39]. No statistical analysis was performed on EMG timings because of the many cases in which no clear inhibitory or excitatory changes could be identified.…”
Section: Data Processingmentioning
confidence: 99%
“…The analysis aimed at highlighting APAs accompanying the first backward displacement of the CoP, which marks the onset of the afferent signals produced by the voluntary recruitment of the gait prime mover muscles. The data analysis approach replicated that used by Marchese et al (2019). In brief, the raw EMG data were high-pass filtered with a zero-phase shift sixth-order elliptic filter and a cut-off frequency of 50 Hz, to remove movement artifacts.…”
Section: Data Processingmentioning
confidence: 99%